"In the 1980s NHS there wasn't today's climate of fear around speaking out"—Allyson Pollock. (7th January 2021) - Mahase, Elisabeth
Abstract : Being a public health doctor means questioning government policy, the Newcastle professor tells Elisabeth Mahase, as she wins a BMJ award for "speaking truth to power"